STUDI KASUS PELAKSANAAN INISIASI MENYUSU DINI DAN BOUNDING ATTACHMENT PADA IBU POST PARTUM DI PUSKESMAS DINOYO KOTA MALANG - Octoclev, Victor Bima (LPPM STIKes Bahrul Ulum Jombang, 2022)
The bounding process on newborns is needed to establish a bond between mother and child that enhances the connection between mother and child at birth and afterwards by giving the mother an Initiation of Early Breastfeeding (IMD). The purpose of this research is for know the bounding attachment on post partum mother by doing IMD immediately after the baby is born. This research using case study type with participative observational methods using two research subjects with focus study of successful infants and IMD infants who are not successful. Interviews and observations are performed using anecdotal record instruments, checklists and ordinal dimension assessment scales. Conducted by doing qualitative analysis, the data presented in the form of narration. The results of the case study showed that, when the IMD the bounding observation on subjects 1 (Mrs. S parietas G9P8Ab000) whose baby successfully performed IMD within 47 minutes with a score of 5, was observed until the third day of post partum got score 7, range score 5-7 (the need for support for bounding is extra) the closeness of the mother and baby is still lacking and needs to be improved. While the bounding observation when the IMD on subject 2 (Mrs. C parietas G3P2Ab000) whose baby failed to perform IMD until 90 minutes with a score of 8, observed until the third day of post partum was score 9, range score 8-10 (requirement of support for bounding is ordinary) that is good mother and baby closeness and need to be keep up. The conclusion of a successful baby and a non-successful baby doing an IMD does not affect the bounding attachment process of the post partum mother. Discussion for further researcher is a similar study focus by adding maternal knowledge criteria and support of health workers when they facilitating IMD maternal parietas multi/grandemultipara against bounding attachment. Keywords: Early Initiation Breastfeeding, Bounding Attachment, Post Partum